Trubacka Republika . Trumpets' Republic - Missio, Stefano; Gori, Alessandro (Gori, Alessandro, 2006)
Verzio FF Submission Gvozden Rosic, leader of a small band in Guča, a village of 5,000 inhabitants in Central Serbia trains for the greatest brass band competition in the world. Used to sound the charge in wartime, the trumpet has lost its military significance and become an emotional part of the life of Serbian people; it is played when children are born and when people marry and move to a new house, but it also escorts the dead in their last journey.